Sources and levels of selenium on breast meat quality of broilers - Boiago, Marcel Manente (2014)
Qualitative characteristics of breast meat of broilers fed diets supplemented with different concentrations (0; 0.3 and 0.5mg kg-1) of selenium in the form of selenomethionine and sodium selenite were analyzed. A total of 1050 one-day-old male Cobb broiler chicks were arranged factorially at random to five treatments (two concentrations x two sources + control diet without addition of selenium) with 7 replications of thirty birds each and received an isonitrogenous and isocaloric diets in all phases according to their ages (1-21, 22-35, and 36-42 days). At 42 days of age, TBARS (thiobarbituric acid reactive substances) after storage at 4ºC for one, seven and 15 days and also after 30 days under freezing temperatures (-15°C), color (CIELab), water holding capacity, cooking loss, shear force, pH and selenium concentration were determined in slaughtered birds breast meat. Results indicated that the use of selenomethionine provides less lightness and lower oxidation in chicken breast meat stored up to 15 days at 4°C. There was a positive effect of dietary different sources and levels of selenium on breast meat quality of broilers. It was observed a linear effect of dietary selenium levels on the amount of selenium deposited in the muscle, and the organic source (selenomethionine) is more effective than inorganic one (sodium selenite) for broiler meat conservation.